New Insights into Platelet Signalling Pathways by Functional and Proteomic Approaches - Jurk, Kerstin; Walter, Ulrich (Hämostaseologie, 2019)
As circulating sentinels of vascular integrity, platelets act as crucial haemostatic cells as well as important inflammatory and immune cells, whereas under pathological conditions platelets drive thrombotic as well as non-thrombotic diseases related to chronic inflammation. In addition, platelets serve as an important cellular model to study the biology and pharmacology of signal transduction pathways. Platelet inhibition and activation responses are mediated by multiple signalling networks, which are tightly regulated by balanced catalysis of protein phosphorylation and dephosphorylation through protein kinases and protein phosphatases, respectively. However, we are only at the beginning of understanding the complexity of interacting signalling pathways and their impact on platelet function. Here, we review current functional and proteomic approaches that lead to novel concepts of understanding the proteome, kinome and phosphatome of human platelets. A more in-depth understanding of both protein kinases and protein phosphatases using human platelets will contribute to evaluate their further diagnostic and therapeutic potential in inflammation- and immune-mediated diseases.
Keywords: platelet signalling; proteomics; protein kinases; protein phosphatases